Pengaruh Harga, Keragaman Produk dan Store Atmosphere terhadap Kepuasan Konsumen pada Kedai Coffee Culture Jombang - Nilasari, Febby; Pujianto, Agung; Nasution, Ute (Universitas 17 Agustus 1945 Surabaya, 2021)
Abstract Now, with so many coffee shops popping up, consumers are free to choose a convenient, attractive coffee shop. Kedai Coffee Culture is one of the businesses in the coffee shop that has been around for a long time in the city of Jombang. Kedai Coffee Culture is known as a place to enjoy simple coffee, affordable prices and a comfortable atmosphere.This study aims to determine and analyze the effect of price, product diversity and store atmosphere both partially and simultaneously on customer satisfaction at Kedai Coffee Culture. This research uses causal associative methods and quantitative approaches. The population used is all consumers of Kedai Coffee Culture with a sample of 96 respondents. Data collection is done by distributing questionnaires. Data analysis using linear multiple regression analysis with the help of SPSS 22.The results of this study prove that price, product diversity and store atmosphere both partially and simultaneously have a positive and significant effect on customer satisfaction at Kedai Coffee Culture. Keyword : Price, Product Diversity, Store Atmosphere.